PENGARUH KUALITAS PRODUK, KEPUASAN HARGA DAN PEMASARAN HIJAU TERHADAP KEPUASAN PELANGGAN MOBIL LCGC TOYOTA AGYA - Bernard Edwin Silaban (ESENSI: Jurnal Manajemen Bisnis, 2018)
Toyota Agya is one of the car categorized with Low Cost Green Car (LCGC), this type of the car has increasing demand in Indonesia especially in Jakarta. These types of car bring the mission and positioning to be environmental friendly. The objective of the research are to see whether The Product Quality, Price Satisfaction and Green Marketing Impact Customer’s Satisfaction of The LCGC Toyota Agya partially and simultaneously. The research concluded that Product Quality, Price Satisfaction and Green Marketing simultaneously Impact Customer’s Satisfaction of The LCGC Toyota Agya. Partially, Product Quality and Green Marketing had significant impacts, but Price Satisfaction is not significant.